THEORETICAL BASICS OF STUDYING LEXICAL TRANSFORMATIONS IN TRANSLATION - Qo’ldoshev O’ktam O’razovich; Ahrorova Sevara (American Journals, 2025)
This article presents an analysis of various conceptual approaches of scientists to the concept of “lexical transformation”, as well as the role of transformation in the development of practical skills of students in learning practice of translation. It explores the unique linguistic nuances and technical terminologies that often pose hurdles in achieving accurate and contextually appropriate translations. Through a thorough literature analysis, this article aims to shed light on the existing methodologies employed to overcome these challenges.
Keywords: Lexical transformation, concrete definition, generalization, antonymous translation, compensation, supplementation, omission.